12-6w=10-5w

Simple and best practice solution for 12-6w=10-5w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-6w=10-5w equation:


Simplifying
12 + -6w = 10 + -5w
Solving
12 + -6w = 10 + -5w
Solving for variable 'w'.
Move all terms containing w to the left, all other terms to the right.
Add '5w' to each side of the equation.
12 + -6w + 5w = 10 + -5w + 5w
Combine like terms: -6w + 5w = -1w
12 + -1w = 10 + -5w + 5w
Combine like terms: -5w + 5w = 0
12 + -1w = 10 + 0
12 + -1w = 10
Add '-12' to each side of the equation.
12 + -12 + -1w = 10 + -12
Combine like terms: 12 + -12 = 0
0 + -1w = 10 + -12
-1w = 10 + -12
Combine like terms: 10 + -12 = -2
-1w = -2
Divide each side by '-1'.
w = 2
Simplifying
w = 2

You can always share this solution

See similar equations:

| 4(3x+5)=10x+2 | | 9x-55+3x+35=180 | | 2(x+10)-6=2 | | 25x-1=9 | | -8m+1-m=12+7 | | 40=64t-16t^2 | | 2y+3+2y=y+6 | | 0=x^4+8x^3-9x^2 | | (3x+7+3x+7)+(4x-2+4x-2)= | | 0.5= | | 2.5+1.3=1.3h-2.3 | | 0.75(8+2y)=3 | | -7(x+2)-43=6-14 | | 12x-3(-4x+3)+5=13 | | -5w+2=15w-10 | | 2x-2=24 | | 6x+152+3x+91=180 | | 3x+10+x-30=180 | | x^2-3x-150=0 | | .07x+.08(4x+32000)=46630 | | 4w*3w+2w=24 | | 25x+6-27x=4-6 | | 2(2b-4)=10-2b | | 11x+9=13(11-x) | | 10y=12-4x | | .5x+10=20 | | (36x^2)-120x=-70 | | -31y=434 | | 14=7x-4+2x | | 5+2(x+8)=-3 | | 19.72+6.5z=4.8z | | 32x+3=40x-3 | | 4x-16=24 | | 15-4x=x-5 | | (8x-10+8x-10)+(6x+6x)= | | 250+16x=210+18x | | 15d-8=2d | | (36x^2)-120=-70 | | 5h+2g=23 | | -14.8+0.2s=-16.4s+19.85+18.7s | | 8-5(2a+3)= | | y=-9-2x | | 8z-1=3z+6 | | |3-2b|=-7 | | |3-2b|=7 | | 8-y=5 | | 70x-35=245 | | 5x+12-2x=36+6x-7x | | -4(x+2)-11=2(-2x-3)-14 | | -15.73-9.3b=16.82-7.2b | | x-3x-150=0 | | 3y+48y=0 | | 3.9k=2.1k+17.1 | | 8=3x+4x-6 | | 11(p-5)-10(6p+22)=-32+38 | | -4y-15=0 | | -2.6r=1.7r+18.92 | | n-9=162 | | (5x+5x)+(3x+6+3x+6)= | | t^2+3t-40=0 | | a+17=4 | | 3*y-7=27 | | 19.4-.6c=-16.6 | | -7x-x=-11-2x | | 9(b-4)-7=5(3b-2) |


Related pages


gcf of 84square root 75 simplifiedderivative of sinx 2greatest to least fractions calculator726.5add improper fractions calculatorwhat is 0.375 as a fractionsimplify the square root of 12198 prime factorizationwhat is the prime factorization of 40010-12.5gcf of 72 and 1081kxmgh equationmcmxcviii convert2y 5x 1prime factorization for 104expand 2x 2y 5simplify 3n x 2pk12elsprime factorization of 135the prime factorization of 84prime factors of 3302x y 4 solve for ygcf of 10510b10300-229calculator for adding fractions23x3derivative of cos 6xprime factorization tableprime factorization of 15125factorization calculatorsqrt 1000gcf of 40 and 64gcf of 1446a squaredprime factorization of 111gcf of 10533-10310.5.5prime factorization for 392x 6y 8tanx cotxsimplify 4x 6x0.4.2derivative of sin 3xx2 4xcommon multiples of 15sin 3t32 prime factorizationroman numerals 1998graph y 4x 86.02x10 23what is 9.5 as a decimalwhat is 3 fourths as a decimalgcf of 120216 prime factorizationgraph 2x 5y 15derivative ln 3xprime factorization of 208252-100ln 4xwhat is the gcf of 100 and 1204.99 dollars2cosx 1 0csc2x 1gcf of 32 and 72cosx cos 2xax4 bx3 cx2 dx e 02log1600 roman numeralsprime factorization of 210700-270cos 3t